2012
DOI: 10.1128/jb.00860-12
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Directly Shunts β-Oxidation Degradation Intermediates into De Novo Fatty Acid Biosynthesis

Abstract: We identified the fatty acid synthesis (FAS) initiation enzyme in Pseudomonas aeruginosa as FabY, a β-ketoacyl synthase KASI/II domain-containing enzyme that condenses acetyl coenzyme A (acetyl-CoA) with malonyl-acyl carrier protein (ACP) to make the FAS primer β-acetoacetyl-ACP in the accompanying article (Y. Yuan, M. Sachdeva, J. A. Leeds, and T. C. Meredith, J. Bacteriol. 194:5171-5184, 2012). Herein, we show that growth defects stemming from deletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 104 publications
2
47
0
3
Order By: Relevance
“…The deuterium-tracing results from this study help to clarify, and suggest specifically, that it is the C 8 -acyl-CoA ␤-oxidation intermediate that is utilized. This is supported by recent evidence showing that P. aeruginosa can directly shunt C 8 -acyl-CoA into the fatty acid synthesis pathway (39).…”
Section: Discussionsupporting
confidence: 73%
“…The deuterium-tracing results from this study help to clarify, and suggest specifically, that it is the C 8 -acyl-CoA ␤-oxidation intermediate that is utilized. This is supported by recent evidence showing that P. aeruginosa can directly shunt C 8 -acyl-CoA into the fatty acid synthesis pathway (39).…”
Section: Discussionsupporting
confidence: 73%
“…This condensing enzyme performs a task usually attributed to FabH but uses a Cys-His-His active site of FabB/FabF enzymes (Yuan et al, 2012b). The fabY mutant is still viable indicating a possible alternative secondary mechanism of FAS in P. aeruginosa (Yuan et al, 2012a). It exhibits a growth defect and a decreased production of quorum sensing signaling molecules, rhamnolipids and siderophores (Yuan et al, 2012b).…”
Section: Genementioning
confidence: 98%
“…The PA3286 shunt mechanism endows P. aeruginosa with a unique metabolic capacity among bacteria for FAS initiation using C8-CoA primer obtained directly from degradation of exogenous fatty acid (11,54). Deuterated fatty acid labeling studies have shown that all cellular demands for FAS can be met via the PA3286 shunt provided exogenous fatty acids C8 and longer are present in the medium (11), including for acylation of lipid A and hence the reestablishment of wild-type antibiotic susceptibility. There is a rich supply of long-chain fatty acids in human serum (55), thus the PA3286 shunting mechanism could bypass the function of FabY in vivo and prevent lipid A from being hypoacylated.…”
Section: Discussionmentioning
confidence: 99%
“…The ⌬fabY phenotype is characterized by muted quorum sensing and diminished siderophore secretion (8), a finding consistent with the need for FAS intermediates in the synthesis of the three major acylated quorum-sensing signal molecules [2-heptyl-3-hydroxy-4-quinolone (PQS), N-(3-oxododecanoyl)-L-homoserine lactone, and N-butanoyl-L-homoserine lactone] (9) and in siderophore assembly (10). Residual FAS initiation in the absence of fabY is thought to be due in part to the ␤-ketoacyl-ACP synthase PA3286, a KASIII family condensing enzyme with low catalytic activity when using short-chain acetyl-CoA as an initiating substrate (11). The main cellular role for PA3286 in wild-type P. aeruginosa, however, is in the shunting of exogenous fatty acidCoA degradation intermediates from the catabolic ␤-oxidation pathway into FAS at the octanoyl-CoA (C8-CoA) substrate chain length through condensation with malonyl-ACP to form decanoyl-ACP (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation